The limit state of steel beams research of damaged building elements (Academic journal Industrial Machine Building Civil Engineering, 2023)
The article is devoted to the study of the limit state of steel І-beams under buckling with operational geometric imperfections revealed during inspections of damaged elements of reconstructed buildings. The influence of damage in the form of initial curvature in the horizontal plane on the stability and bearing capacity of structures is analyzed. The possibility of using bearing capacity resources, namely lateral bracing restraint with the help of structures attached to a steel beam, is considered. The proposed approaches are aimed at optimizing the use of materials and increasing savings by detailing the verification calculations of damaged steel beams.
Keywords: buckling; I-beam; initial curvature; operational geometric imperfections; restraint